DESAIN CETAKAN PELEK 15 INCH UNTUK MOBIL PENUMPANG DENGAN MATERIAL ALUMINIUM MENGGUNAKAN SOFTWARE PENGECORAN - Bayu Bagaskara (2020)
The rim is an important part of driver safety in determining the direction of speed on a vehicle. Rims that have high quality not only pay attention to its beauty but also must pay attention in terms of function and reliability of the rim. The high quality is influenced by the rim manufacturing process to be made. In the car rim manufacturing process using metal casting methods. The process of making car rims is mostly done by forging or semi solid forging, but this method requires a relatively expensive cost, another way to make a car rim is by gravity die casting method using a permanent mold. In this research conducted by modeling the rim cast product in 3D, then casting software and actual simulations, as well as applying different design molds using the riser and not using the riser, and the pad system. The use of riser and pad systems aims to minimize shrinkage defects in cast products. From this study the data obtained from software simulation results and validation from experiments in the form of the location and percentage of shrinkage defects that occur in cast products with a riser system and do not use the riser system and the system. From this data, conclusions can be drawn regarding the use of a very effective riser system to prevent shrinkage defects in permanent mold casting with A356 aluminum material.